Mometasone furoate hydrogel for scalp use: in vitro and in vivo evaluation. (August 2014) - Salgado, Ana; Raposo, Sara; Marto, Joana; Silva, Alexandra N.; Simões, Sandra; Ribeiro, Helena M.
Abstract Dermatological inflammatory diseases often affect the scalp and the eyebrows. Common dosage forms available on the market for those situations are lotions; however, the presence of hair limits their use. Gels, for their consistency and adhesiveness, are a suitable alternative to the lotions in these situations. The aim of this study was to develop a new stable gel containing mometasone furoate (MF), with anti-inflammatory activity and a controlled delivery, to improve topical treatment of scalp dermatitis. Pharmaceutical development, physical and chemical characterization, stability, in vitro release and permeation studies and in vivo anti-inflammatory activity were performed. The gel presented an acidic pH and an apparent viscosity of 35 Pa.s. The microbiological analysis showed that the results were within the established specification limits. The release and the permeation profiles suggest that the drug is mainly retained in the upper skin layers. MF gel was tested in an animal model of cutaneous inflammation and presented similar anti-inflammatory activity compared to a commercially available MF dosage form. The gel was chemically, physically and microbiologically stable. The results suggest that the developed hydrogel formulation containing MF can be of actual value for improving the clinical effectiveness in the treatment of scalp dermatitis.